2011
DOI: 10.4103/0259-1162.94757
|View full text |Cite
|
Sign up to set email alerts
|

Do pencil-point spinal needles decrease the incidence of postdural puncture headache in reality? A comparative study between pencil-point 25G Whitacre and cutting-beveled 25G Quincke spinal needles in 320 obstetric patients

Abstract: Background:Postdural puncture headache (PDPH) is a distressing complication of the subarachnoid block. The previous studies conducted, including the recent ones, do not conclusively prove that pencil-point spinal needles decrease the incidence of PDPH. In this study, we have tried to find out whether a pencil-point Whitacre needle is a better alternative than the classic cutting beveled, commonly used, Quincke spinal needle, in patients at risk of PDPH.Materials and Methods:Three hundred and twenty obstetric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…Although it has been in practice for a long time, newer varieties of needles are in use now a days with which incidence of adverse effects have drastically come down. 9 These new needles have revolutionised the techniques of the procedure because of which the success rate of the procedure has also improved. 9,10 Most Anaesthesiologists are familiar with Quincke needle which is commonly available in many of the hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been in practice for a long time, newer varieties of needles are in use now a days with which incidence of adverse effects have drastically come down. 9 These new needles have revolutionised the techniques of the procedure because of which the success rate of the procedure has also improved. 9,10 Most Anaesthesiologists are familiar with Quincke needle which is commonly available in many of the hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…9 These new needles have revolutionised the techniques of the procedure because of which the success rate of the procedure has also improved. 9,10 Most Anaesthesiologists are familiar with Quincke needle which is commonly available in many of the hospitals. In spite of the better features of newer needles like Whitacre, Quincke is possibly the preferred needle due to its easy availability and lesser cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear definition is not provided Pal (2011) Headache experienced in the frontal or occipital region exacerbated by sitting or standing position and reduced or relieved by lying down and may be accompanied by nausea, vomiting, neck stiffness, diplopia, and tinnitus.…”
Section: Siddiqui (2012)mentioning
confidence: 99%
“…Nine studies (11 comparisons, 1313 participants) reported the failure of spinal anesthesia. 14,16,17,22,39,43,[45][46][47] There was no statistically significant difference of the pooled incidence of failure of spinal anesthesia between the pencil-point SN and the cutting-bevel SN (RR = 1.28, 95% CI 0.56 to 2.93; P = 0. 55, I 2 = 0%).…”
Section: Failure Ratementioning
confidence: 99%